A review into the Islamic tradition in the Mughal garden: (Re) shaping our stand on Islamic art and design - Abdul Latiff, Zainab; Mohd. Yaman, Maheran (Malaysian Institute Of Planners, 2017)
In the field of garden history, Mughal gardens represent a prominent chapter of what is often called the Islamic garden tradition. Most previous studies have discussed on its theories and principles.However,it is essential to establish the physical characteristics of the Mughal garden as representing Islamic garden tradition. The method of content analysis has been applied in this study. The study found that Mughal garden design is much influenced by the Persian’s Chāhār Bāgh, Hindu mythologyand Quranic paradise imagery. To conclude, Mughal garden design needs to be assimilated into the current culture of local people within the established principles of environment in Islam.